Investigating the internal erosion behavior and microscopic mechanisms of chemically stabilized soil: an experimental study - Zhang, Buping; Zhu, Xinghua; Tao, Xuewen; Wang, Mengkui; Asghar, Aamir; Mi, Guoliang (Frontiers in Earth Science, 2024)
IntroductionInternal erosion triggered by water pipeline leaks seriously threatens the stability of the urban ground. Hangzhou, a city in Zhejiang Province, China, is facing critical challenges due to urban ground collapse (UGC) caused by internal erosion. However, there is a lack of research on the prevention of UGC by improving the internal erodibility of underground soil. Addressing this issue is of utmost importance to ensure the city’s stability and safety. This paper proposes to improve the internal erodibility of typical sandy silt soils with chemical stabilisers.MethodsThe effects of three chemical stabilisers, lignosulphonate (LS), lime (LI), and lignin fibre (LF), on the critical shear stress (τc) and erosion coefficient (kd) of sandy silt soils were investigated, which from Hangzhou, Zhejiang, China, by the hole erosion test (HET) at different mixing amounts and at different conservation times.ResultsThe findings indicate that LF mainly improves the erosion resistance of sandy silt by increasing τc, and the maximum increase is 2.38 times; LI mainly improves the erosion resistance by decreasing kd, and the maximum decrease is 2.18 times. After adding LS, τc and kd did not change significantly. The scanning electron microscope (SEM) test revealed that the inclusion of LF led to the formation of larger agglomerates in the sandy silt soil. The microstructure of sandy silt soil remained dispersed even after adding LS. Various chemical stabilisers used to improve sandy silt soils exhibited distinct erosion mechanisms. Sandy silt soils improved with LF exfoliated into agglomerates, displaying high resistance to erosion. On the other hand, the sandy silt treated with LF still lacks a protective layer and shows minimal improvements in its ability to withstand erosion. In contrast, the LS-amended sandy silt remains stripped with individual soil particles with insignificant changes in erosion resistance.DiscussionThis study can provide a conceptual framework for choosing foundation treatment techniques in future urban development projects.